The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1002/chem.201404300
|View full text |Cite
|
Sign up to set email alerts
|

Chlorination of Two Isomers of C86 Fullerene: Molecular Structures of C86(16)Cl16, C86(17)Cl18, C86(17)Cl20, and C86(17)Cl22

Abstract: Chlorination of a mixture of C86 isomers no. 16 (Cs ) and no. 17 (C2 ) with VCl4 or a (TiCl4 +Br2 ) mixture afforded crystalline chlorides with 16 to 22 Cl atoms per fullerene cage. Single crystal X-ray diffraction with the use of synchrotron radiation enabled us to determine the chlorination patterns of C86 (16)Cl16 , C86 (17)Cl18 , C86 (17)Cl20 , and C86 (17)Cl22 . At these degrees of chlorination, addition patterns of C86 (16) and C86 (17) chlorides have some features in common, owing to the close similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
(62 reference statements)
2
8
0
Order By: Relevance
“…We note in passing that free energy differences at elevated temperatures have been proposed as more relevant for describing detailed fullerene isomer distributions as generated by arc discharge. 64 For C n (82 r n r 108) several isomers have been isolated from soot extracts for each n. 4,6,[12][13][14][15][16][17][18][19][20][21][22][23][24][25]65 In most cases the lowest energy isomers of these agree within 0.4% with our experimental CCS value. For C 82 , Achiba 4 identified two isomers, C 82 (7) with C 3v symmetry and C 82 (9) with C 2v symmetry.…”
Section: àsupporting
confidence: 57%
See 2 more Smart Citations
“…We note in passing that free energy differences at elevated temperatures have been proposed as more relevant for describing detailed fullerene isomer distributions as generated by arc discharge. 64 For C n (82 r n r 108) several isomers have been isolated from soot extracts for each n. 4,6,[12][13][14][15][16][17][18][19][20][21][22][23][24][25]65 In most cases the lowest energy isomers of these agree within 0.4% with our experimental CCS value. For C 82 , Achiba 4 identified two isomers, C 82 (7) with C 3v symmetry and C 82 (9) with C 2v symmetry.…”
Section: àsupporting
confidence: 57%
“…In the size range below C 110 , a large number of isomers has been structurally characterized in condensed phase by different methods such as NMR and X-ray diffraction -without (below C 98 ) or with (above C 88 ) functionalization. [4][5][6][7][12][13][14][15][16][17][18][19][20][21][22][23][24][25] With the DFT and trajectory method procedure outlined above (method 4), we calculated the CCS values for the geometry optimized charged fullerene structures corresponding to those isomeric carbon cage connectivities which have been observed in condensed phase and compared them with the experimental CCS values, see Table 3 and Fig. 4.…”
Section: àmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, two very similar molecules, C 94 (133)Cl 20 and C 94 (133)Cl 22 , overlap in the same crystallographic site, thus resulting in an averaged composition of C 94 Cl 21.67 . Such a kind of cocrysallization typical for polychloro derivatives of higher fullerenes has also been observed in the crystal structures of C 76 Cl 24–34 and C 86 Cl 18–22 …”
supporting
confidence: 56%
“…6b However, the whole scheme of the branched cage transformation of C 88 (33) presented in Figure 2 is an exceptional case in which all transformation steps are experimentally determined unambiguously rather than deduced by a reconstruction of the pathway. Recently, another case of a branched skeletal transformation of C 86 (16) was reported that consisted, however, from two interchangeable C2Ls and the same final chloride of C 82 ( NC 2) 6d…”
mentioning
confidence: 99%